The modulatory effects of caffeic acid on human monocytes and its involvement in propolis action - Bufalo, Michelle Cristiane [UNESP]; Sforcin, Jose Mauricio [UNESP] (Wiley-Blackwell, 2015)
Objectives: Researchers have been interested in investigating the mechanisms of action of propolis and the compounds involved in its biological activity; however, the effect of its isolated constituents on human immune cells still deserves investigation. Thus, this study aimed to verify the action of caffeic acid on human monocytes in an attempt to verify its effects on the innate immunity, and to analyse its participation in propolis activity. Methods: Monocytes viability was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide method after incubation with caffeic acid. Cell markers expression by monocytes (Toll-like receptors (TLR)-2, TLR-4, human leukocyte antigen (HLA)-DR and CD80) was analysed by flow cytometry. TNF- and IL-10 production was determined by enzyme-linked immunosorbent assay and the activity of monocytes against Candida albicans was investigated after incubation with different concentrations of caffeic acid. Key findings: Caffeic acid downregulated TLR-2 and HLA-DR expression and inhibited cytokine production whereas it upregulated the fungicidal activity of monocytes, without affecting cell viability. Conclusions: Caffeic acid exerted an immunomodulatory action in human monocytes in the evaluated parameters depending on concentration, with no cytotoxic effects. Moreover, it was partially involved in propolis action.
Keywords: Caffeic acido-stimulatory molecules; Cytokine; Propolis; Toll-like receptors